Spatial transcriptomic characterization of COVID-19 pneumonitis identifies immune circuits related to tissue injury - Cross, AR; de Andrea, CE; María, V-E; Landecho Acha, MF; Cerundolo, L; Weeratunga, P; Etherington, R; Denney, L; Ogg, G; Ogg, G; Ho, LP; Roberts, ISD; et al. (American Society for Clinical Investigation, 2023)
Severe lung damage in COVID-19 involves complex interactions between diverse populations of immune and stromal cells. In this study, we used a spatial transcriptomics approach to delineate the cells, pathways and genes present across the spectrum of histopathological damage in COVID-19 lung tissue. We applied correlation network-based approaches to deconvolve gene expression data from areas of interest within well preserved post-mortem lung samples from three patients. Despite substantial inter-patient heterogeneity we discovered evidence for a common immune cell signaling circuit in areas of severe tissue that involves crosstalk between cytotoxic lymphocytes and pro-inflammatory macrophages. Expression of IFNG by cytotoxic lymphocytes was associated with induction of chemokines including CXCL9, CXCL10 and CXCL11 which are known to promote the recruitment of CXCR3+ immune cells. The tumour necrosis factor (TNF) superfamily members BAFF ( TNFSF13B ) and TRAIL ( TNFSF10 ) were found to be consistently upregulated in the areas with severe tissue damage. We used published spatial and single cell SARS-CoV-2 datasets to confirm our findings in the lung tissue from additional cohorts of COVID-19 patients. The resulting model of severe COVID-19 immune-mediated tissue pathology may inform future therapeutic strategies. One Sentence Summary Spatial analysis identifies IFNγ response signatures as focal to severe alveolar damage in COVID-19 pneumonitis.